HUBUNGAN TINGKAT PENGETAHUAN IBU HAMIL TENTANG HIV/AIDS DENGAN SIKAP TERHADAP PROVIDER INITIATED TEST AND COUNSELLING (PITC) DI PUSKESMAS SLEMAN YOGYAKARTA - Yuriah, Siti (STIKES Abdurahman. Pusat Informasi dan Manajemen, 2024)
Human Immunodeficiency Virus is a virus that attacks the human immune system. Whereas, Acquired Immunodeficiency Syndrome is a number of symptoms of a disease that results in a decrease in the immune system. HIV and AIDS is a global public health problem, if it is not immediately treated, it will have complications such as tuberculosis, cryptococcal meningitis, bacterial infections, lymphomas, Kaposi's sarcoma and even death. HIV infection in pregnant women can spread to their babies. Primary Health Center of Sleman Yogyakarta had 2 HIV positive pregnant women registered as patients in 2018 which were detected from the results of the PITC test. This study aimed to determine the relationship between the level of knowledge of pregnant women and attitudes towards PITC at Primary Health Center of Sleman Yogyakarta. The research was a quantitative research with Cross Sectional approach. The population was 312 pregnant women and 76 of them were taken as respondents who had given the PITC examination. The sampling technique was done by Quota Sampling on all pregnant women. Data were analysed through bivariate analysis using Kendall Tau. The results showed that there was a significant relationship between the level of knowledge of pregnant women about HIV / AIDS and attitudes toward PITC at Sleman Primary Health Center of Yogyakarta with p value (0.001) and r correlation coefficient of 0.360 which indicated a low closeness relationship. Most of respondents had a good level of knowledge about HIV / AIDS and had a good attitude towards PITC. Midwives are expected to be able to convince pregnant women to undergo HIV / AIDS screening and increase promotion of HIV / AIDS.